2009
DOI: 10.1002/hbm.20698
|View full text |Cite
|
Sign up to set email alerts
|

Volume and iron content in basal ganglia and thalamus

Abstract: Magnetic resonance imaging (MRI) studies have highlighted the possibility to investigate brain iron content in vivo. In this study, we combined T2* relaxometry and automatic segmentation of basal ganglia based on T1-weighted images in healthy subjects, with the aim of characterizing age related changes in volume and iron-related relaxivity values (R2*) of these structures. Thirty healthy subjects underwent MR imaging at 3 Tesla. Mean R2* values and volumes were calculated for the selected subcortical structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
81
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 44 publications
17
81
1
Order By: Relevance
“…In contrast, the GP result with QSM, whilst rich in iron in absolute terms, did not demonstrate an age-related increase. The high R2* values for the GP (independent of age) in contrast to thalamus, caudate and putamen are consistent with previous in vivo R2* reports and post-mortem correlations with iron concentration (Gelman et al, 1999;Langkammer et al, 2010;Péran et al, 2009;Yao et al, 2009). Furthermore, agerelated increase in R2* have been reported previously in the GP in some studies (Callaghan et al, 2014;Draganski et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, the GP result with QSM, whilst rich in iron in absolute terms, did not demonstrate an age-related increase. The high R2* values for the GP (independent of age) in contrast to thalamus, caudate and putamen are consistent with previous in vivo R2* reports and post-mortem correlations with iron concentration (Gelman et al, 1999;Langkammer et al, 2010;Péran et al, 2009;Yao et al, 2009). Furthermore, agerelated increase in R2* have been reported previously in the GP in some studies (Callaghan et al, 2014;Draganski et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…To date, the T2* transverse relaxation time, or its inverse rate, R2* (=1/T2*), has been routinely utilised as a surrogate marker to assess brain iron deposition with both in vivo (Gelman et al, 1999;Péran et al, 2009;Yao et al, 2009) and post mortem data (Langkammer et al, 2010), demonstrating a linear relationship between R2* and iron concentration in deep grey matter (GM). R2*, however, is known to be a composite measure sensitive to T2/diffusion effects and magnetic field inhomogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…The location of iron accumulation was further associated with microstructural axonal damage. Recently, several studies reported a linear relationship between transverse magnetic resonance relaxation rates and iron content in healthy subjects and postmortem tissue, indicating that R2* imaging is a good surrogate for detecting cerebral iron accumulations 25, 26, 27. By a rater‐driven approach, T2*‐weighted imaging of SAH patients in their chronic stage allowed to identify signal alterations within the subarachnoid space even years after the onset 28, 29, 30.…”
Section: Discussionmentioning
confidence: 99%
“…T 2 *-Weighted Images Processing T 2 *-weighted volumes were post processed according to previously published methods Peran et al 2009). Briefly, the 6 T 2 *-weighted volumes were averaged to generate a mean T 2 *-weighted volume.…”
Section: Dti Processingmentioning
confidence: 99%